Impact of social media data on postmarket safety evaluation of medicines: a literature review on automatic mining initiatives of adverse drug reactions - Mendes, Ana Catarina Simões Martins (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence